2022
DOI: 10.1093/nar/gkac287
|View full text |Cite
|
Sign up to set email alerts
|

Pre-mRNA splicing factor U2AF2 recognizes distinct conformations of nucleotide variants at the center of the pre-mRNA splice site signal

Abstract: The essential pre-mRNA splicing factor U2AF2 (also called U2AF65) identifies polypyrimidine (Py) tract signals of nascent transcripts, despite length and sequence variations. Previous studies have shown that the U2AF2 RNA recognition motifs (RRM1 and RRM2) preferentially bind uridine-rich RNAs. Nonetheless, the specificity of the RRM1/RRM2 interface for the central Py tract nucleotide has yet to be investigated. We addressed this question by determining crystal structures of U2AF2 bound to a cytidine, guanosin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…The associations between this editing and splicing event may be attributed to the co-regulations of RNA binding proteins, such as DHX9 , PRPF8 and U2AF2 . Their involvements in alternative splicing and RNA editing have been showed in previous studies (39,60,79,80). According to these analyses, we could further expand the functions of RNA editing QTLs from diverse aspects of phenotype changes.…”
Section: Resultssupporting
confidence: 62%
“…The associations between this editing and splicing event may be attributed to the co-regulations of RNA binding proteins, such as DHX9 , PRPF8 and U2AF2 . Their involvements in alternative splicing and RNA editing have been showed in previous studies (39,60,79,80). According to these analyses, we could further expand the functions of RNA editing QTLs from diverse aspects of phenotype changes.…”
Section: Resultssupporting
confidence: 62%
“…Considering that FOXP3 introns have C-rich/U-poor py tracts and that these py tracts serve as poor substrates for U2AF2 binding (Sickmier et al, 2006;Glasser et al, 2022), it was not surprising that we observed significantly less U2AF2 binding to F3i11wt-tobra compared to F3i11pUtobra (Figure 3C). U2AF2 directly interacts with SF1, which binds the BPS, and U2AF1, which binds the 3'SS so it was also not surprising that we detected less binding of both proteins on F3i11wt-tobra compared to F3i11pU-tobra (Figure 3C).…”
Section: Discussionmentioning
confidence: 87%
“…The intronic variant c.866-34_866-8del is close to the 3′splice acceptor site of intron 8, and the pyrimidine content of the deleted sequence (CUU​AUC​UCC​CUC​UCU​CUC​UCU​CUC​UCC) is higher than 96%, which suggests that this sequence is likely to be located in the polypyrimidine tracts region in pre-mRNA. The absence of polypyrimidine tracts may interfere with the functioning of certain splicing factors and induce abnormal splicing ( Auweter and Allain, 2008 ; Glasser et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%